Benefits of a Paleolithic diet with and without supervised exercise on fat mass, insulin sensitivity, and glycemic control: a randomized controlled trial in individuals with type 2 diabetes. Issue 1 (30th June 2016) - Otten, Julia; Stomby, Andreas; Waling, Maria; Isaksson, Andreas; Tellström, Anna; Lundin‐Olsson, Lillemor; Brage, Søren; Ryberg, Mats; Svensson, Michael; Olsson, Tommy
Abstract: Background: Means to reduce future risk for cardiovascular disease in subjects with type 2 diabetes are urgently needed. Methods: Thirty‐two patients with type 2 diabetes (age 59 ± 8 years) followed a Paleolithic diet for 12 weeks. Participants were randomized to either standard care exercise recommendations (PD) or 1‐h supervised exercise sessions (aerobic exercise and resistance training) three times per week (PD‐EX). Results: For the within group analyses, fat mass decreased by 5.7 kg (IQR: −6.6, −4.1; p  < 0.001) in the PD group and by 6.7 kg (−8.2, −5.3; p  < 0.001) in the PD‐EX group. Insulin sensitivity (HOMA‐IR) improved by 45% in the PD ( p  < 0.001) and PD‐EX ( p  < 0.001) groups. HbA1c decreased by 0.9% (−1.2, −0.6; p  < 0.001) in the PD group and 1.1% (−1.7, −0.7; p  < 0.01) in the PD‐EX group. Leptin decreased by 62% ( p  < 0.001) in the PD group and 42% ( p  < 0.001) in the PD‐EX group. Maximum oxygen uptake increased by 0.2 L/min (0.0, 0.3) in the PD‐EX group, and remained unchanged in the PD group ( p  < 0.01 for the difference between intervention groups). Male participants decreased lean mass by 2.6 kg (−3.6, −1.3) in the PD group and by 1.2 kg (−1.3, 1.0) in the PD‐EX group ( p  < 0.05 for the difference between intervention groups). Conclusions: A Paleolithic diet improves fat mass and metabolic balance including insulin sensitivity, glycemic control, and leptin in subjects with type 2 diabetes. Supervised exercise training may not enhance the effects on these outcomes, but preserves lean mass in men and increases cardiovascular fitness. Copyright © 2016 John Wiley & Sons, Ltd.